Epenthesis and deletion as strategies to acquire complex syllabic structures: Strategies in the Interlanguage of Brazilian learners of German as a foreign language. (June 2021) - Pereira, Rogéria Costa
Abstract: This research aimed to discuss strategies to reformulate complex syllabic constituents (initial onsets and final codas) in the Interlanguage of Brazilian learners of German as a foreign language. The comparison of the phonotactics from both languages led to the hypothesis that Brazilian learners have difficulties in producing these constituents and, therefore, develop different strategies to accommodate the German syllabic structure to the syllabic mold of Brazilian Portuguese. Five types of initial onsets (consisting of up to three consonants) and nine of final codas (consisting of up to four consonants) were analyzed through the variables, proficiency level and style change (obtained from reading a list of words, a list of sentences and the report of a comic). The correlation between the variables in the selection of three types of strategies was explored: deletion from an element, epenthesis (prothesis, anaptyxis and paragoge), and L–vocalization. The results showed that proficiency level and style of task influence the selection of the modification strategy.